Gingival condition and tooth‐brushing behavior after alcohol consumption. (23rd September 2014) - Mizutani, S.; Ekuni, D.; Tomofuji, T.; Yamane, M.; Azuma, T.; Iwasaki, Y.; Morita, M.
<x xml:space="preserve">Abstract</x> Background and Objective Various studies have reported the relationship between alcohol consumption and gingival condition. However, they focus on the direct effects of alcohol consumption or alcohol sensitivity on gingival condition, and it is unclear how oral health behaviors relate these relationships. The aims of this study were to assess the inter‐relationships between gingival condition, tooth‐brushing behavior after drinking alcohol and alcohol sensitivity in university students who drink more than once per week on average. Material and Methods A total of 808 students (541 males, 267 females) that habitually consume alcohol were analyzed. The disease activity of gingival condition was assessed as the percentage of bleeding on probing (%BOP). Additional information regarding alcohol sensitivity and oral health behaviors, including tooth‐brushing behavior after drinking, were also collected. Results Thirteen percent of the current participants reported neglecting tooth‐brushing after drinking, and their alcohol consumption was higher than those who did not neglect tooth‐brushing. Logistic regression analysis showed that high %BOP (%BOP ≥ 20) was associated with male (OR = 1.53; 95% CI, 1.01–2.33), neglect of tooth‐brushing after drinking (OR = 2.60; 95% CI, 1.20–5.61) and debris index (OR = 8.38; 95% CI, 4.24–16.60) in participants with low alcohol sensitivity. In participants with high alcohol sensitivity, high %BOP was associated with debris index (OR = 7.60; 95% CI, 3.12–18.51), but not with any oral health behaviors. Conclusions The study revealed that alcohol consumption was indirectly related to gingival disease activity through the neglect of tooth‐brushing after drinking alcohol in university students with low alcohol sensitivity.